Simulations of Muon Flux in Slanic Salt Mine - Mehmet Bektasoglu; Halil Arslan; Denis Stanca (Advances in High Energy Physics)
Geant4 simulation package was used to simulate muon fluxes at different locations, the floor of UNIREA mine and two levels of CANTACUZINO mine, of Slanic Prahova site in Romania. This site is specially important since it is one of the seven sites in Europe that are under consideration of housing large detector components of Large Apparatus studying Grand Unification and Neutrino Astrophysics (LAGUNA) project. Simulations were performed for vertical muons and for muons with a zenith angle θ≤60°. Primary muon flux and energies at ground level were obtained from previous measurements. Results of the simulations are in general agreement with previous simulations made using MUSIC simulation program and with the measurements made using a mobile detector.